Moderasi Beragama dalam Perspektif Sinodalitas Paus Fransiskus - Amuna, Yohanes Candra Sekar Bayu Putra (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2025)
This study aims to analyze religious moderation from the perspective of Pope Francis' synodality. The researcher will use Pope Francis' framework on synodality to explore the paradigm of religious moderation in Indonesia and reveal its relevance to the socio-religious dimension of Indonesian society. Through the idea of ​​synodality, Pope Francis offers a more inclusive way of living the faith. Researchers will utilize qualitative methods with a descriptive-analytical approach. Research on this theme will be carried out first by dissecting the conceptual study of religious moderation and explaining the essence of synodality then offering a conception of religion inclusively as a path towards religious moderation. From this study, researchers found that religious moderation can be applied in society if religious people also participate actively in developing creative, innovative, and transformative new ways. In this context, every religion needs to be given the opportunity to reveal its characteristics in diversity.